Assessing video-based health education in African contexts: a systematic review - Impito, Pinto Francisco; Azevedo, José (Frontiers in Communication, 2025)
IntroductionHealth education is vital for empowering patients with knowledge about their health conditions, treatment options, and self-care, enabling them to make informed decisions. Video-based Health Education (VbHE) has proven to be a powerful tool for enhancing health literacy, often outperforming traditional methods in various circumstances. Previous research has focused on specific diseases in low-resource settings, but a broader understanding of video applications and implementation challenges remains necessary. This systematic review assessed the use of video for health education purposes in the least developed African countries from 2020 to 2024, exploring insights into the types of health content delivered through video, their effectiveness, and implementation obstacles.MethodsWe searched the ScienceDirect, PubMed, Scopus, Google Scholar, PLOS, and AJOL databases, limiting our review to the UN’s 33 least-developed African countries. Studies were evaluated based on country, participants, sample sizes, intervention methods, duration, video delivery, educational emphasis, objectives, outcomes, and findings. Adhering to PRISMA guidelines ensured a structured methodology.ResultsFrom the 218 records identified, 15 studies met our inclusion criteria. These studies highlighted video interventions with a focus on cancer (n = 5, 33.3%), HIV (n = 3, 20%), maternity care (n = 5, 33.3%), and other areas (n = 2, 13.3%, including COVID-19 and spinal anesthesia procedures). Most studies (n = 13, 86.6%) showed videos positively influenced knowledge retention and health outcomes, while the remaining two (n = 2, 13.3%) noted no significant difference from traditional methods. Video dissemination methods featured mobile devices, TV screens, and online platforms, with intervention durations ranging from 30 min to 36 months. Of the included studies, video has proven effective in enhancing health education in the least-developed African nations.DiscussionChallenges including connectivity issues, cultural adaptation, and digital literacy remain significant. This review highlights the critical role of mobile video health communication in empowering underserved populations and informs future strategies to optimize health outcomes in resource-constrained African Contexts.